La proporcionalidad constitucional en las sanciones administrativas con respecto a las infracciones ambientales estipuladas en los Artículos 323, 324, 325 y 326 del Código Orgánico del Ambiente - Carrillo Jaramillo, Yesenia Fernanda (2023)
The present investigation carries out an analysis of the problem that exists with respect to the non-proportionality of the administrative sanctions imposed on environmental infractions typified in the Organic Code of the Ecuadorian Environment, in Articles 323, 324, 325 and 326; regarding the variables of the fine for environmental infractions and the scales of the fines referring to minor, serious and very serious administrative infractions in environmental matters. That they do not establish the sanctioning regime for environmental infractions, under the premise of the Constitution of the Republic of Ecuador, which under the principle of constitutional supremacy, normative guarantees and the right to legal certainty; establishes that legal rules or laws must maintain conformity with the constitutional provision of proportionality. The fines imposed caused by environmental infractions are not proportional, since it is taken into account for the establishment of the same, only the Income Tax declarations caused by the offender; and what I propose should be determined in the sanctions, is the proportionality to the environmental damage caused by the offender, as well as the real proportionality of the economic capacity of the offender; since if we only guide ourselves in the taxes declared to the Internal Revenue Service, these do not reflect in the background the economic capacity of the offender; Rather, the same should be equated in guarantee of the Right to Legal Security, taking other elements that will allow us to be more equitable and proportional in the sanctions. Pretending through a Project, to present a proposal to reform the Organic Code of the Environment in what respects the sanctions of environmental infractions, in a clear, practical and possible way; This was satisfactorily verified thanks to the verification of the problem through the development of the selective dissemination of information and scientific doctrinal theoretical literature; In addition, with the application of the techniques of surveys and interviews, verification of objectives and practical contrast of the hypothesis, verifying the existence of the problem raised, applying methods and techniques of a scientific nature that served to obtain results and substantiate the proposal to reform the Organic Code of the Environment.